(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The textile industry is one of the largest contributors to global industrial waste and pollution. This comprehensive review examines the various types of waste generated across the textile production lifecycle, from raw material processing to post-consumer disposal. The article classifies these wastes into two main categories: pre-consumer waste (including spinning waste such as carding droppings and short fibers, as well as roving and weaving waste) and post-consumer waste (discarded garments and textiles). Using the IMRAD structure, it details the characteristics and generation points of each waste type. Furthermore, it analyzes their profound environmental effects, including landfill accumulation, water pollution from chemical leaching and microplastic shedding, and greenhouse gas emissions. The study concludes by evaluating current recycling strategies and underscores the critical necessity of transitioning from a linear "take-make-dispose" model to a Circular Economy framework. This transition, supported by technological innovation and sustainable design principles, is presented as the only viable path for mitigating the environmental impact of the textile industry.